Managing EC2 and VPC : AWS with Python and Boto3 series - Erdoğan, Niyazi (PACKT Publishing, 2019)
Learn: You'll be able to implement any sort of infrastructure on AWS with Python using VPCs, Subnets and EC2s! You'll learn how to code against AWS API using Python and Boto3! You'll learn how to launch EC2 Instances on AWS using Python and Boto3! You'll learn how to isolate and control your own infrastructure with Python using Route Tables, Internet Gateways, Security Groups and Rules! You'll have very good understanding of VPC concepts like Subnets, Route Tables and Internet Gateways by putting all into real-world practice with Python code! You'll be confident to work with AWS APIs using Python for any kind of AWS Resource on VPC and EC2 Instances! You'll learn how to read and code against an API documentation! You'll be able to launch your own infrastructure on AWS without even signing-in to AWS! About: In this course, we'll start by taking a look at the tools and the environment that we need to work with AWS resources. We will teach you how you can set up your environment on both MacOS and Windows. Once we're ready with our environment setup, we'll start implementing our solution on AWS. Then we will create two subnets.